Molecular epidemiology of extended-spectrum beta-lactamase-producing-Klebsiella species in East Tennessee dairy cattle farms - Gelalcha, Benti D.; Mohamed, Ruwaa I.; Gelgie, Aga Edema; Kerro Dego, Oudessa (Frontiers in Microbiology, 2024)
The rising prevalence of Extended-Spectrum Beta-Lactamase (ESBL)-producing Klebsiella species (spp.) poses a significant threat to human and animal health and environmental safety. To address this pressing issue, a comprehensive study was undertaken to elucidate the burden and dissemination mechanisms of ESBL-Klebsiella spp. in dairy cattle farms. Fifty-seven Klebsiella species were isolated on CHROMagar™ ESBL plates and confirmed with MADLI-TOF MS and whole genome sequenced from 14 dairy farms. Six families of beta-lactamase (bla) (blaCTX-M, blaSHV, blaTEM, blaOXY, blaOXA, and blaSED) were detected in ESBL-Klebsiella spp. genomes. Most (73%) of isolates had the first three types of beta-lactamase genes, with blaSHV being the most frequent, followed by blaCTX-M. Most (93%) isolates harbored two or more bla genes. The isolates were genotypically MDR, with 26 distinct types of antibiotic resistance genes (ARGs) and point mutations in gyrA, gyrB, and parC genes. The genomes also harbored 22 different plasmid replicon types, including three novel IncFII. The IncFII and Col440I plasmids were the most frequent and were associated with blaCTXM-27 and qnrB19 genes, respectively. Eighteen distinct sequence types (STs), including eight isolates with novel STs of K. pneumoniae, were detected. The most frequently occurring STs were ST353 (n=8), ST469 (n=6), and the novel ST7501 (n=6). Clusters of ESBL-Klebsiella strains with identical STs, plasmids, and ARGs were detected in multiple farms, suggesting possible clonal expansion. The same ESBL variant was linked to identical plasmids in different Klebsiella STs in some farms, suggesting horizontal spread of the resistance gene. The high burden and dual spread mechanism of ESBL genes in Klebsiella species, combined with the emergence of novel sequence types, could swiftly increase the prevalence of ESBL-Klebsiella spp., posing significant risks to human, animal, and environmental health. Immediate action is needed to implement rigorous surveillance and control measures to mitigate this risk.